PENGARUH SUKU BUNGA THE FED, HARGA MINYAK DAN INFLASI TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA - Akua Miyanti, Gusti Ayu Diah; Wiagustini, Luh Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
Rise and fall of the price of a stock is strongly influenced by the economic conditions of a country. Price has an important role in influencing consumer decisions in buying a product including stocks. The purpose of this study was to examine the effect of Fed interest rate, oil price and inflation on Indonesian Joint Stock Price Index from January 2012 to December 2016. This research is an associative research that aims to determine the influence or relationship between two variables or more. Data processed using computer software that is SPSS (Statistical Package for Social Science). The test result through Multiple Linear regression analysis shows that the Fed interest rate, oil price and inflation simultaneously have a significant effect on the Composite Stock Price Index. Partially, the interest rate of the Fed has a significant positive effect on the Composite Stock Price Index in BEI, while the price of oil has a significant negative effect and inflation has no effect on JCI period 2012 -2016.